1983
DOI: 10.5271/sjweh.2405
|View full text |Cite
|
Sign up to set email alerts
|

Nasal and sinonasal cancer. Connection with occupational exposures in Denmark, Finland and Sweden.

Abstract: or from the hospitals (Denmark). Those still alive who agreed to an interview (N = 167) were individually matched for age and sex with patients with colonic or rectal cancer. A detailed telephone interview was made according to standardized forms. Both cases and referents thought that their condition was the one under study. The exposures were coded blindly by an industrial hygienist. The results showed associations between nasal and sinonasal cancer and exposure to (i) hardwood or mixed wood dust (discordant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1
8

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 12 publications
2
58
1
8
Order By: Relevance
“…Nasal and sinonasal tumors have been associated with exposure to stainless steel welding fumes (9), but no such tumors were observed in the present study.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Nasal and sinonasal tumors have been associated with exposure to stainless steel welding fumes (9), but no such tumors were observed in the present study.…”
Section: Discussioncontrasting
confidence: 51%
“…Asbestos (2,21) and hexavalent chromium (22) are two possible causative agents. A well-conducted case-referent study has revealed an increased incidence of nasal and sinonasal tumors among welders exposed to chromium (9).…”
mentioning
confidence: 99%
“…Thereby we could obtain valid population-based estimates of the excess risk of work-related mortality. For example, in the estimation of the attributable fraction for nasal cancer, we applied the RR estimate of 2.4 for nickel exposure, taken from a Nordic case-referent study (261). In that study, the cases were derived from national registration systems, rather than from the corresponding greater RR estimate of 8.7 from a smaller cohort study of nickel refinery workers (43).…”
mentioning
confidence: 99%
“…Relative risks well in excess of 5Á10 in the boot and shoe manufacturing industries have been reported [74]. Shoe and leather workers are exposed to dust from leather and to benzene from the glue [75]. In the earlier Nordic study based on census occupations and follow-up from 1971Á1991 [1], shoe and leather workers experienced the highest risk of nasal cancer with an SIR of 2.94 (95% CI 1.47Á5.26).…”
Section: Cancer Of the Nose And Nasal Sinusesmentioning
confidence: 99%